PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP PENINGKATAN HASIL BELAJAR EKONOMI PADA SISWA KELAS X - 1 SMA NEGERI 1 PRAJEKAN MATERI POKOK KEBUTUHAN - Nurul Azise; Nursalam Nursalam (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2017)
Base early observation and yielding interview by learns economy at SMAN 1 Prajekan, gotten by that information at class X-1 result studies student still haven't accomplished Minimal Thoroughness Criterion. Besides is gotten that method that utilized by tend teacher utilizes discourse, so student perceives saturated to study and there are many material which was complete. This research intent to increase and completes economic studying result student braze X-1 through learning model implements Jigsaw type on subject “KEBUTUHAN” discussion. This observational type is Observational Action braze. Observational activity in one cycle is done through 4 phases which is planning, action performing, observation, reflection. If was successful, done by succeeding cycle. Data collecting via interview, essay, observation, and documentation. Result observationaling to point out that on kognitif's domain on alae I. cycle classical is 78,57% but yielding those are still haven't accomplished ala thoroughness percentage klasikal where klasikal's thoroughness already been established is 85% therefore researcher drawn out to go to cycles II. and yielding learned one is reached is 96,43%. On afektif's domain I. cycle as big as 75% and cycles II. as big as 97,5%. For psikomotor's domain I. cycle as big as 80% and cycles II. as 100%. With so gets to be concluded that learnings model implements Jigsaw types can increase and complete economic student studying results student braze X-1 SMAN 1 Prajekan on subject “KEBUTUHAN” discussion. Base observational result already we do it, therefore our tips is implemented model Jigsaw type learning can make alternative in teaching by espoused supportive learning media, e.g. charta so student not saturated and passive at within class. By use of type learning model this Jigsaw student becomes to be motivated, active, and innovative and creative because agreeable class condition. It visually on yielding step-up studies student on cycle II. which is 96,43% as compared to studying result on I. cycle which is 78,57%, so also on afektif's aspect and psikomotor is student.